Acute effects of a loaded warm-up protocol on change of direction speed in professional badminton players - Maloney, S. J.; Turner, A. N.; Miller, S. C. (Journal of Applied Biomechanics, 2014)
It has previously been shown that a loaded warm-up may improve power performances. We examined the acute effects of loaded dynamic warm-up on change of direction speed (CODS), which had not been previously investigated. Eight elite badminton players participated in three sessions during which they performed vertical countermovement jump and CODS tests before and after undertaking the dynamic warm-up. The three warm-up conditions involved wearing a weighted vest (a) equivalent to 5% body mass, (b) equivalent to 10% body mass, and (c) a control where a weighted vest was not worn. Vertical jump and CODS performances were then tested at 15 seconds and 2, 4, and 6 minutes post warm-up. Vertical jump and CODS significantly improved following all warm-up conditions (P < .05). Post warm-up vertical jump performance was not different between conditions (P = .430). Post warm-up CODS was significantly faster following the 5% (P = .02) and 10% (P < .001) loaded conditions compared with the control condition. In addition, peak CODS test performances, independent of recovery time, were faster than the control condition following the 10% loaded condition (P = .012). In conclusion, the current study demonstrates that a loaded warm-up augmented CODS, but not vertical jump performance, in elite badminton players.